2015
DOI: 10.1097/yct.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

Depression Severity in Electroconvulsive Therapy (ECT) Versus Pharmacotherapy Trials

Abstract: This selective literature review confirms that patients who entered ECT clinical trials were more severely ill than those who entered the selected comparator pharmacotherapy trials. Such data highlight the critical role of ECT in the treatment of severe and treatment-resistant mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
0
20
1
1
Order By: Relevance
“…Replication of our findings in a larger ECT sample would be valuable. With about one‐third being moderately depressed, the patients in our study were, on average, somewhat less severely depressed (HDRS17 of 24.8) than the rates reported in most ECT studies (HDRS17 of 27.6 ). Due to the observational design of our study, our sample inevitably comprised a combination of severely depressed patients with an acute ECT indication and depressed patients with often less severe but longer‐lasting depressive symptoms that had proved resistant to multiple antidepressant treatments.…”
Section: Discussioncontrasting
confidence: 53%
“…Replication of our findings in a larger ECT sample would be valuable. With about one‐third being moderately depressed, the patients in our study were, on average, somewhat less severely depressed (HDRS17 of 24.8) than the rates reported in most ECT studies (HDRS17 of 27.6 ). Due to the observational design of our study, our sample inevitably comprised a combination of severely depressed patients with an acute ECT indication and depressed patients with often less severe but longer‐lasting depressive symptoms that had proved resistant to multiple antidepressant treatments.…”
Section: Discussioncontrasting
confidence: 53%
“…Some studies in Poland and Slovakia revealed that ECT is primarily indicated for affective disorders like depression [3], while schizophrenia was the main indication for ECT in eastern Europe and Asia [4]. A recent study found that ECT is used more often than medications in severe cases of depression [5]. Several studies did not find any serious side effects of ECT such as epilepsy, brain damage, and pain [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Neuromodulatory interventions include ECT, magnetic seizure therapy, repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS), vagal nerve stimulation (VNS), and deep brain stimulation (DBS). ECT is considered the first-line treatment for more severe forms of depression (Kellner et al, 2014). Recent MRI studies indicate that ECT may increase brain connectivity in depression, demonstrated by neuroplasticity of white matter microstructure suggesting increased fiber integrity of dorsal fronto-limbic pathways involved in mood regulation (Lyden et al, 2014).…”
Section: How the Neuroscience Of Depression Can Inform Interventionmentioning
confidence: 99%